2011
DOI: 10.1177/003335491112600611
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Respiratory Symptoms and Environmental Exposures among Children and Adolescents following Hurricane Katrina

Abstract: Children and adolescents affected by Hurricane Katrina experienced environmental exposures associated with increased prevalence of reported URS and LRS. Additional research is needed to investigate the long-term health impacts of Hurricane Katrina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Despite limitations, our results may help inform postdisaster health services delivery and predisaster mitigation planning; clinicians and disaster planners should be aware that demand for asthma-related health care may rise among survivors, as suggested by previous research (Ohkouchi et al, 2013;Rath et al, 2011), and that those experiencing PTSD avoidance symptoms may be at particular risk.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Despite limitations, our results may help inform postdisaster health services delivery and predisaster mitigation planning; clinicians and disaster planners should be aware that demand for asthma-related health care may rise among survivors, as suggested by previous research (Ohkouchi et al, 2013;Rath et al, 2011), and that those experiencing PTSD avoidance symptoms may be at particular risk.…”
Section: Discussionmentioning
confidence: 76%
“…The prevalence of asthma and other respiratory symptoms increases in the aftermath of natural disasters (e.g., Ohkouchi et al., ; Rath et al., ). Disrupted access to medication (Hendrickson, Vogt, Goebert, & Pon, ) and physical triggers such as contaminated air (Rando, Lefante, Freyder, & Jones, ) have been identified as postdisaster asthma risk factors.…”
mentioning
confidence: 99%
“…Numerous studies have confirmed higher concentrations of mold spores in the indoor air of houses flooded during Hurricane Katrina. Asthma-like respiratory symptoms were the major associated health issue (Solomon et al, 2006;Rao et al, 2007;Barbeau et al, 2010), however other upper and lower respiratory symptoms and neuro-ophthalmic symptoms also have been reported from children and adults affected by Hurricane Katrina (Rath et al, 2011;Sridhar et al, 2012). Moreover, several published studies have assessed the mycotoxins found in dust samples from homes during the post-Hurricane Katrina period (Bloom et al, 2009;Chung et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 , 27 ] While there was no increase in ARI in this study, this has occurred in the setting of multiple cases among a single population,[ 30 ] and possibly in association with increased environmental exposures. [ 31 ] This study had an increased number of presentations with skin infections. While theoretically sound, there is surprisingly little previous published data to support this.…”
Section: Discussionmentioning
confidence: 99%